(untitled) (Comparative & International Education Series, 2021)
Chapter 4|16 pages International Students at Canadian Community Colleges: Origins, Evolution, and Current Trends ByOleg Legusov, Hayfa F. Jafar This study uses the interview approach to document analysis for an examination of historical and emerging trends involving international students at Canadian community colleges. The findings show that the provinces’ cultural differences and immigration policies significantly affect the number of international students on college campuses. Moreover, the current approach to immigrant selection may have contributed to the reconfiguration of the colleges’ international student body, which has gone from mostly Chinese to predominantly Indian. Furthermore, the study explores new approaches used to increase the market share of international students, such as campuses exclusively for international students and partnerships with private career colleges. It also gives a brief analysis of the latest development, namely the shift to online instruction in response to the COVID-19 pandemic. The study highlights the importance of understanding these trends to address the emerging challenges effectively.